Nasionalisme Lokal Elite Jawa Timur dalam Krisis Pemerintahan Republik Indonesia Tahun 1948 – 1950 - Ari Sapto (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2012)
The Second Dutch Military Aggression led to several leaders of the Republic of Indonesia trapped in captivity. This incident created a crisis for the government of the Republic of Indonesia. In East Java, the political constellation before and during the government crisis was characterized by the struggle of few elites. In the struggle it seemed that the local cultural values are influential in the way of looking at problems facing the nation and made reference to the behavior of elites. In East Java, the crisis of governance that took place during the National Revolution shows the resurgence of local cultural values.